The Risk of Recurrent Venous Thromboembolism in Patients with and without Factor V Leiden - Eichinger, Sabine; Pabinger, Ingrid; Stümpfien, Andreas; Hirschl, Mirko; Bialonczyk, Christine; Schneider, Barbara; Mannhalter, Christine; Minar, Erich; Lechner, Klaus; Kyrle, Paul A (Thrombosis and Haemostasis, 1997)
Thromboprophylaxis with oral anticoagulants up to six months is established in patients after a first venous thromboembolic event (VTE). The risk of recurrent VTE is still considerable thereafter, and it is uncertain whether some patients might benefit from extended anticoagulation. We performed a prospective, multicenter trial (4 thrombosis centers) and evaluated in 380 patients with a first or recurrent VTE (patients with a deficiency of antithrombin, protein C, protein S or plasminogen; cancer; or an antiphospholipid antibody syndrome were excluded) the risk of recurrence after discontinuation of secondary thromboprophylaxis with oral anticoagulants. It was the aim of the study to evaluate whether patients with factor V Leiden are at an increased risk of recurrent VTE. 112 (29.5%) patients were carriers of factor V Leiden (26.9% heterozygous, 2.6% homozygous). After a median observation time of 19.3 months the overall recurrence rate of VTE was 9.9%. Recurrent deep vein thrombosis and/or pulmonary embolism occurred in 26 of 268 patients without factor V Leiden (9.7%) and in 10 of 112 patients with factor V Leiden (8.9%). The probability of recurrent VTE two years after discontinuation of oral anticoagulants was 12.4% (95% Cl 7.8-17) in patients without factor V Leiden and was 10.6% (95% Cl 3.8-17.4) in carriers of the mutation. This difference was statistically not significant. Patients with factor V Leiden are not at a higher risk of recurrent VTE within two years after discontinuation of oral anticoagulants than patients without factor V Leiden. Balancing the risk of recurrent VTE and bleeding from oral. anticoagulants, patients with factor V Leiden are not likely to benefit from oral anticoagulant therapy extended beyond six months.